Observation of collisionless shocks in a large current‐free laboratory plasma. Issue 21 (3rd November 2014) - Niemann, C.; Gekelman, W.; Constantin, C. G.; Everson, E. T.; Schaeffer, D. B.; Bondarenko, A. S.; Clark, S. E.; Winske, D.; Vincena, S.; Van Compernolle, B.; Pribyl, P.
Abstract We report the first measurements of the formation and structure of a magnetized collisionless shock by a laser‐driven magnetic piston in a current‐free laboratory plasma. This new class of experiments combines a high‐energy laser system and a large magnetized plasma to transfer energy from a laser plasma plume to the ambient ions through collisionless coupling, until a self‐sustained MA∼ 2 magnetosonic shock separates from the piston. The ambient plasma is highly magnetized, current free, and large enough (17 m × 0.6 m) to support Alfvén waves. Magnetic field measurements of the structure and evolution of the shock are consistent with two‐dimensional hybrid simulations, which show Larmor coupling between the debris and ambient ions and the presence of reflected ions, which provide the dissipation. The measured shock formation time confirms predictions from computational work.